The Impact of Entrepreneurial Marketing toward Work Perfromance at the Centre of Garut Specialty Food - Tasya Kahfia Abshariena; Sisca Eka Fitria (Jurnal Ilmu Sosial Politik dan Humaniora (Jisora), 2019)
The MSMEs is a sector that has a very large role in increasing the economic growth of the Indonesta state. Garut Regency of West Java utilizing the wealth and potential they have by making MSMEs as employment. One factor that has a very umportant role in the development of MSMEs is precisely the Dodol Industry itself is marketing but there are still many who use traditional marketing. This study aims to analyze the influence of Entrepreneurial Marketing on business performance at dodol centers in Garut Regency. This study aims to determine the effect of Opportunity Focus, Proactiveness, Customer Intensity, Innovation, Risk Taking, Resource Leveraging, and Value Creation on Business Performance. The population in this study were business actors in the dodol center of Garut Regency, which amounted to 156 business actors with a sample of 70 respondents. This study uses a non-probability sampling technique that is Purposive sampling. The data analysis technique in this study is descriptive with data analysis of Structural Equation Model-Partial Least Square by performing data processing using SMART-PLS 3.0. The results of this study are that Customer Intensity, Innovation, Risk Taking, Resource Leveraging, and Value Creation have a significant effect on Business Performance, while Opportunity Focus and Proactiveness have no significant effect on Business Performance. From the r-square results that the seven independent variables witch is Entrepreneurial Marketing simultaneously contribute influence of 60.1%, which has moderate value.